Analisis Tingkat Pertumbuhan Aset Pada BPRS Muamalat Harkat Kecamatan Sukaraja Kabupaten Seluma - Pramadeka, Katra; Astuti, Budi; Lova, Venty Amara (Faculty of Economics and Islamic Business, UIN Fatmawati Sukarno Bengkulu, 2021)
The assets growth rate is influenced by several factors, namely internal factors and external factors. By considering these factors, Muamalat Syariah Financing Bank (SFB) Harkat Bengkulu has a strategy so that can always increase from year to year. The strategy used is to develop market share in the form of multi-purpose financing. The problem in this study is, are there any factors that influence the asset growth rate in Muamalat Harkat SFB Sukaraja District, Seluma Regency and what factors influence the assets growth rate in Muamalat Harkat SFB Sukaraja District, Seluma Regency. This study uses qualitative data and uses observation, interviews and documentation as data collection instruments. The results of this study indicate that in increasing asset growth, there are internal factors that consist of employee job performance, job spirits, job discipline, SOP, inspection from Financial Services Authority (FSA/OJK) and internal audit. While the external factors consist of the level of public trust that has begun to grow in the form of savings or deposits, financing, and inspection from external audits.